2023
DOI: 10.17305/bb.2023.9049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the latest advancements in physical therapy techniques for treating cervical spondylosis patients: A narrative review

Abstract: Cervical spondylosis is a widespread medical condition that significantly impacts patients' quality of life. Treatment options include surgical and conservative approaches, with conservative treatment often being the preferred choice. Rehabilitation therapy is an essential component of conservative treatment, and advancements in technology have the way to the development of new physiotherapy techniques. The effectiveness of treatment largely hinges on the patient's ability to improve their dysfunction. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, the Global Burden of Disease 2010 Study revealed neck pain as the fourth factor causing disability [ 17 ] and inducing psychosocial problems, especially stress-related issues such as depression, anxiety, and fear of movement [ 2 ], resulting in seriously declined quality of life. Consequently, CS treatment mostly involves pain alleviation and retardation of disease progression [ 18 , 19 ]. Current guidelines for first-line treatment of CS recommend nonsteroidal anti-inflammatory drugs (NSAIDs), which, however, have severe adverse reactions, and their prolonged use is not recommended [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the Global Burden of Disease 2010 Study revealed neck pain as the fourth factor causing disability [ 17 ] and inducing psychosocial problems, especially stress-related issues such as depression, anxiety, and fear of movement [ 2 ], resulting in seriously declined quality of life. Consequently, CS treatment mostly involves pain alleviation and retardation of disease progression [ 18 , 19 ]. Current guidelines for first-line treatment of CS recommend nonsteroidal anti-inflammatory drugs (NSAIDs), which, however, have severe adverse reactions, and their prolonged use is not recommended [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%